D3 and CoffeeScript - Gopal, Nikhil; Safari eBooks ([Place of publication not identified] : O'Reilly Media, 2014)
"Create powerful data visualizations by learning how to use CoffeeScript and D3. With this fast-paced video course, you'll leverage your knowledge if Python syntax to pick up the basics of CoffeeScript, the language that compiles to JavaScript. Then you'll tackle the fundamentals of the D3 JavaScript library for implementing visualizations that are attractive, well designed, interactive, and updatable in real-time."--Resource description page.
Title from resource description page (viewed November 24, 2014).
Presenter, Nikhil Gopal.
Keywords: CoffeeScript (Computer program language); Information visualization; Electronic books